Short-term outcomes after spleen-preserving minimally invasive distal pancreatectomy with or without preservation of splenic vessels: a Pan-European retrospective study in high-volume centers - Korrel, Maarten; Lof, Sanne; Al Sarireh, Bilal; Björnsson, Bergthor; Boggi, Ugo; Butturini, Giovanni; Casadei, Riccardo; De Pastena, Matteo; Esposito, Alessandro; Fabre, Jean Michel; Ferrari, Giovanni; Fteriche, Fadhel Samir; et al. (Annals of surgery, 2023)
Objective: - To compare short-term clinical outcomes after Kimura and Warshaw MIDP. - Background: - Spleen preservation during distal pancreatectomy can be achieved by either preservation (Kimura) or resection (Warshaw) of the splenic vessels. Multicenter studies reporting outcomes of Kimura and Warshaw spleen-preserving MIDP are scarce. - Methods: - Multicenter retrospective study including consecutive MIDP procedures intended to be spleen-preserving from 29 high-volume centers (≥15 distal pancreatectomies annually) in 8 European countries. Primary outcomes were secondary splenectomy for ischemia and major (Clavien-Dindo grade ≥III) complications. Sensitivity analysis assessed the impact of excluding (“rescue”) Warshaw procedures which were performed in centers that typically (>75%) performed Kimura MIDP. - Results: - Overall, 1095 patients after MIDP were included with successful splenic preservation in 878 patients (80%), including 634 Kimura and 244 Warshaw procedures. Rates of clinically relevant splenic ischemia (0.6% vs 1.6%, P = 0.127) and major complications (11.5% vs 14.4%, P = 0.308) did not differ significantly between Kimura and Warshaw MIDP, respectively. Mortality rates were higher after Warshaw MIDP (0.0% vs 1.2%, P = 0.023), and decreased in the sensitivity analysis (0.0% vs 0.6%, P = 0.052). Kimura MIDP was associated with longer operative time (202 vs 184 minutes, P = 0.033) and less blood loss (100 vs 150 mL, P < 0.001) as compared to Warshaw MIDP. Unplanned splenectomy was associated with a higher conversion rate (20.7% vs 5.0%, P < 0.001). - Conclusions: - Kimura and Warshaw spleen-preserving MIDP provide equivalent short-term outcomes with low rates of secondary splenectomy and postoperative morbidity. Further analyses of long-term outcomes are needed.
Gesehen am 20.03.2023